2018
DOI: 10.1177/1178223418792247
|View full text |Cite
|
Sign up to set email alerts
|

Formin Proteins FHOD1 and INF2 in Triple-Negative Breast Cancer: Association With Basal Markers and Functional Activities

Abstract: Basal-like breast cancer is an aggressive form of breast cancer with limited treatment options. The subgroup can be identified immunohistochemically, by lack of hormone receptor expression combined with expression of basal markers such as CK5/6 and/or epidermal growth factor receptor (EGFR). In vitro, several regulators of the actin cytoskeleton are essential for efficient invasion of basal-like breast cancer cell lines. Whether these proteins are expressed in vivo determines the applicability of these finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…However the basal expression of INF2 and FHOD1 may be as important. Both INF2 and FHOD1 have earlier been found to participate in migration or invasion and to be upregulated in clinical cancer tissues in basal-like breast cancer [15], and FHOD1 has additionally been found expressed in oral squamous cell carcinoma and melanoma, also with participation in migration/invasion in vitro [13,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However the basal expression of INF2 and FHOD1 may be as important. Both INF2 and FHOD1 have earlier been found to participate in migration or invasion and to be upregulated in clinical cancer tissues in basal-like breast cancer [15], and FHOD1 has additionally been found expressed in oral squamous cell carcinoma and melanoma, also with participation in migration/invasion in vitro [13,20].…”
Section: Discussionmentioning
confidence: 99%
“…From this cohort, we analyzed the 93 samples that had an integrated diagnosis of glioblastoma, IDH-wildtype according to the WHO 2016 classification [ 14 ]. The slides were stained by the streptavidin-peroxidase method; using a Labvision staining device (Thermo Fisher Scientific, Fremont, CA) with a Bright Vision Poly-HRP-anti-mouse/rabbit kit (Immunologic, Duiven, the Netherlands) as described previously [ 15 ]. Briefly, antigen retrieval for INF2 staining was carried out by microwaving the slides in a pH 9 buffer.…”
Section: Methodsmentioning
confidence: 99%
“…In a study on the MDA-MB−231 and BT−549 TNBCs (triple-negative breast cancer) cell lines, Heuser et al have found that low levels of FHOD1 inhibited cell proliferation and migration. 32 Similarly, studies conducted by Jurmeister et al on breast cancer cells with a reduced level of FHOD1 allowed to present its importance in the context of EMT. The author has shown that FHOD1 regulates MLC2, which expression stimulates SRF-dependent transcription while silencing of FHOD1 significantly affects the disturbance and reduction of intracellular accumulation of G-actin, which reduces the motor properties of cells.…”
Section: Discussionmentioning
confidence: 97%
“… 52 In the case of basal-like breast cancer tissue, the high level of FHOD1 was also presented. 32 Clinical trials show that an increase in mortality in patients with oncological diseases is often associated with the formation of metastases. 4 The actin network is involved in this process, while its dynamic is determined by the proteins accompanying microfilaments like formin.…”
Section: Discussionmentioning
confidence: 99%
“…Formin homology two domain-containing protein one or FHOD1, is a crucial regulator of cellular actin dynamics [6]. Previous studies by us and others implicate FHOD1 as an essential participant in cancer cell migration, invasion, and stress fiber formation [7][8][9][10]. FHOD1 has been implicated as one of the crucial genes linked with advanced disease and metastasis in GC patients [11].…”
Section: Introductionmentioning
confidence: 99%